PCR Amplification of DNA Sequence of Bovine Papillomavirus Type 2 in Urinary Bladder of Cattle with Enzootic Hematuria in Espirito Santo, Brazil - Sousa, Dyeime Ribeiro de; Archanjo, Anderson Barros; Ignacchiti, Mariana Drummond Costa; Pereira Júnior, Olavo dos Santos; Madureira, Ana Paula; Nunes, Louisiane de Carvalho (Brazilian Journal of Veterinary Pathology, 2014)
The goal of this study was to investigate the presence of bovine papillomavirus type 2 (BPV-2) genomic DNA using polymerase chain reaction (PCR) assays, in the urinary bladder of cattle with bovine enzootic hematuria (BEH), in the neoplastic and non-neoplastic lesions in Espírito Santo, Brazil. Thus, 46 bladders with gross BEH lesions were collected from adult cattle at slaughterhouses. The samples were divided into two portions: one for use in histopathological analysis and the other one for PCR. Microscopic analysis showed that 56.52% of the bladders presented neoplastic lesions, of which 50% were benign, 23.08% were malignant and 26.92% presented both types of neoplasms. The remaining 43.48% of the bladders did not show any neoplasms. Presence of BPV-2 was confirmed in 43.48% of the bladders: 65% of these were found in neoplastic lesions and 35% in non-neoplastic lesions. Among the neoplastic lesions, detection of BPV-2 was more frequent in benign lesions (53.84%), followed by malignant lesions (23.08%) and by those presenting both benign and malignant lesions (23.08%). These results confirm the presence of BPV-2 in both neoplastic and non-neoplastic conditions in urinary bladders of cattle with enzootic hematuria from the studied geographic area.